Effect of Smoking Cessation on the Pharmacokinetics and Pharmacodynamics of Clopidogrel after PCI: The Smoking Cessation Paradox Study - Ramotowski, Bogumił; Gurbel, Paul A.; Tantry, Udaya; Bracha, Jan S.; Karaźniewicz-Łada, Marta; Lewandowski, Zbigniew; Budaj, Andrzej (Thrombosis and Haemostasis, 2020)
Background Cigarette smoking is associated with enhanced clopidogrel effect and platelet inhibition. However, the effect of smoking cessation on clopidogrel pharmacokinetics (PK) and pharmacodynamics (PD) is unknown. We aimed to determine the effect of smoking cessation, confirmed by cotinine measurement, on clopidogrel PK and PD after percutaneous coronary intervention (PCI).Methods and Results Following successful PCI, patients treated with 75 mg/day clopidogrel who reported smoking ≥10 cigarettes/day with NicAlert urine cotinine level 6 were enrolled. Clopidogrel and its metabolite concentrations, VerifyNow P2Y12 reaction units (PRUs), and NicAlert levels were measured in the study group before and at 30 days after smoking cessation and in a control group. CYP1A2 and CYP2C19 genotypes were determined. At 30-day visit (n = 87), 45 patients continued smoking, whereas 42 patients stopped smoking. Baseline PRUs were similar between groups. At 30 days, the smoking cessation group had higher PRUs (150.5 ± 68.6 vs. 118.4 ± 65.9, p = 0.03), greater absolute PRU change (27.7 ± 39.8 vs. −12.9 ± 55.4, p = 0.0002), greater change of PRUs adjusted for baseline platelet reactivity (38.6 ± 10.0, p < 0.01), greater risk of high platelet reactivity (HPR) (odds ratio: 10.14 [1.52–67.5], p = 0.017), and a trend towards decreased H3 clopidogrel metabolite levels (−3.41 ng/mL [−11.00 to 0.54 ng/mL], p = 0.072). CYP2C19 LoF carriers who stopped smoking had the highest PRUs, whereas those with the wild type who continued smoking had the lowest PRUs (p < 0.008).Conclusion Smoking cessation in clopidogrel-treated patients after PCI is associated with increased platelet reactivity and greater risk of HPR. Alternative P2Y12 inhibitors may be considered in selected patients who stop smoking after PCI.
Keywords: clopidogrel; platelet reactivity; smoking